Trirubidium hydrogen selenate - A.V.Belushkin, Frank Lab of Neutron Physics, JINR, 141 980 Dubna, Russian Federation (My University, 1993)
Inelastic Neutron Scattering spectrum of Trirubidium hydrogen selenate, Rb₃H(SO₄)₂, measured on the TFXA instrument.
Keywords: TFXA